Urban food sharing : rules, tools and networks - Davies, Anna, 1970- (Policy Press shorts. Research., 2019)
Available Open Access under CC-BY-NC licence. Illustrated by global case studies and empirical data, this book explores the history and current practises of food sharing, whilst exploring the impact and potential of such sharing for cities.